(untitled) (Global Journal of Science Frontier Research, 2014)
In this study, aza-Michael reactions between 1-phenylmethanamine and α,β-unsaturated cyclohexenones were investigated, using lipase from Candida antarctica. The reactions were performed in various organic solvents (CH 2 Cl 2 , hexane, MeOH, toluene, THF) under mild conditions, with orbital shaking and microwave irradiation. The reactions showed good results in the presence of CALB, yielding the Michael adducts and imines. The reaction products were analyzed by GC-MS and in some cases it was found that the reverse aza-Michael reaction had occurred.